Modeling and fabricating a prototype of a thermoelectric generator system of heat energy recovery from hot exhaust gases and evaluating the effects of important system parameters. (5th March 2018) - Mostafavi, Seyed Alireza; Mahmoudi, Mojtaba
Highlights: A thermoelectric module with a low thermal conductivity is more effective. System efficiency could be improved by using liquids on the cold and hot side of TEG. The thermal conductivity of the heat sinks has no significant effect on efficiency. The good results have been yielded, especially at temperatures lower than 100 °C. Abstract: The heat lost through smokestacks has an adequate energy recovery capacity. A new and effective method of recovering this energy is the use of thermoelectric generators, which directly convert thermal energy to electricity. Some of the advantages of thermoelectric generators include their environmental friendliness and also their lack of moving or rotating parts, which makes them operate without noise and extends their service life. This paper deals with the general modeling of a thermoelectric generator system, including the modeling of the cooling system for the cold side of thermoelectric generator, system of heat transfer from smokestack to the hot side of thermoelectric generator and also the modeling of the thermoelectric modules themselves. In continuation, for validating the obtained equations, an experimental prototype of this thermoelectric generator is fabricated and the empirical results including the nominal voltage, current and power of the manufactured system are compared with the theoretical results. This comparison shows the validity of the presented modeling and the good agreement between the theoretical and practical results, especially at low temperatures. Based on the calculations, the highest error was 4.6 percent for a temperature difference of lower than 100 °C. Additionally, for the same temperature difference, the highest theoretical and practical output powers for this module were 3.4 W and 2.8 W, respectively. Considering the matching of these results, the effects of some important parameters on the output power of the considered thermoelectric generator are also investigated, and the significant influence of the thermal conduction coefficient of thermoelectric modules is demonstrated.